1989
DOI: 10.1017/s0952523800011962
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adenosine uptake and endogenous adenosine-containing cells in mammalian retina

Abstract: Autoradiographic techniques were used to label [ 3 H]-adenosine and [ 3 H]-cyclohexyladenosine accumulating cells in rabbit, mouse, and ground squirrel retinas. Immunohistochemical methods revealed the distribution of cells that stained for endogenous adenosine. Comparisons of these two markers revealed for all three species that the distribution of specific subpopulations of retinal cells that store or accumulate the purine nucleoside, adenosine, is similar. For all three species, cells localized in the gangl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…Retinal ganglion cells may also be the source of adenosine that acts on these receptors (Braas et al . 1987; Blazynski et al . 1989), suggesting that adenosine may be a co‐transmitter released from ganglion cell terminals and, by modulating calcium currents on the terminals of ganglion cell, control the release of glutamate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinal ganglion cells may also be the source of adenosine that acts on these receptors (Braas et al . 1987; Blazynski et al . 1989), suggesting that adenosine may be a co‐transmitter released from ganglion cell terminals and, by modulating calcium currents on the terminals of ganglion cell, control the release of glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…A 1 adenosine receptors have been identified within the mammalian retina and were localized to the optic nerve fiber layer, the ganglion cell layer and the inner plexiform layer (Braas et al . 1987; Blazynski et al . 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Perez and Bruun (1987) have also reported that certain of the cell bodies in the GCL that accumulate [ 3 H]-adenosine are also labeled for GABA-like immunoreactivity. We had previously demonstrated that a large number of cell bodies localized to the GCL were labeled by an antisera generated against a derivative of adenosine (Blazynski et al, 1989;Braas et al, 1987). We have now identified these labeled cells as both true ganglion cells and displaced amacrine cells, and demonstrate that, of the latter group of cells, many are also labeled for GAD-like immunoreactivity and accumulate the dye DAPI, a marker for cholinergic cells in the rabbit retina.…”
Section: Introductionmentioning
confidence: 77%
“…Since ganglion cells comprise about two-thirds of the cells in the GCL (Vaney, 1980), then approximately half of the remaining displaced amacrine cells may have been labeled for these two markers. Thus, within this subset of displaced amacrine cells localized within the GCL, uptake systems for GABA (Mosinger & Yazulla, 1985), adenosine (Ehinger & Perez, 1984;Blazynski et al, 1989), and choline (Masland et al, 1984a) have been demonstrated. In addition, as seen in Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation